A Corticotropin Releasing Factor Network in the Extended Amygdala for Anxiety - Pomrenze, Matthew B.; Tovar-Diaz, Jorge; Blasio, Angelo; Maiya, Rajani; Giovanetti, Simone M.; Lei, Kelly; Morikawa, Hitoshi; Hopf, F. Woodward; Messing, Robert O. (The Journal of neuroscience, 2019)
The central amygdala (CeA) is important for fear responses to discrete cues. Recent findings indicate that the CeA also contributes to states of sustained apprehension that characterize anxiety, although little is known about the neural circuitry involved. The stress neuropeptide corticotropin releasing factor (CRF) is anxiogenic and is produced by subpopulations of neurons in the lateral CeA and the dorsolateral bed nucleus of the stria terminalis (dlBST). Here we investigated the function of these CRF neurons in stress-induced anxiety using chemogenetics in male rats that express Cre recombinase from a Crh promoter. Anxiety-like behavior was mediated by CRF projections from the CeA to the dlBST and depended on activation of CRF1 receptors and CRF neurons within the dlBST. Our findings identify a CRF CeA →CRF dlBST circuit for generating anxiety-like behavior and provide mechanistic support for recent human and primate data suggesting that the CeA and BST act together to generate states of anxiety. SIGNIFICANCE STATEMENT Anxiety is a negative emotional state critical to survival, but persistent, exaggerated apprehension causes substantial morbidity. Identifying brain regions and neurotransmitter systems that drive anxiety can help in developing effective treatment. Much evidence in rodents indicates that neurons in the bed nucleus of the stria terminalis (BST) generate anxiety-like behaviors, but more recent findings also implicate neurons of the CeA. The neuronal subpopulations and circuitry that generate anxiety are currently subjects of intense investigation. Here we show that CeA neurons that release the stress neuropeptide corticotropin-releasing factor (CRF) drive anxiety-like behaviors in rats via a pathway to dorsal BST that activates local BST CRF neurons. Thus, our findings identify a CeA→BST CRF neuropeptide circuit that generates anxiety-like behavior.